Variation of Saliva Sampling Procedures in Detecting SARS-CoV2 with Real Time Polymerase Chain Reaction: A Scoping Review - Dewi Suryani; Devi Rahmadhona; Prima Belia Fathana; Indah Sapta Wardani; Ika Nurfiria Tauhida; Mohammad Rizki (Unram Medical Journal, 2022)
Background: Currently there is a rise in the study of saliva as alternative clinical samples for the detection of SARS-CoV2 as it is considered less invasive, able to be obtained independently by patients and does not cause discomfort compared to nasopharyngeal swab (NPS). Nevertheless, there has been an inconsistency of methods applied in sample collection, storage and laboratory assay from previous research. As the pre analytical phase may influence diagnostic result, therefore this scoping review would like to identify the varation approach of saliva collection methods conducted by previous studies. Study Design: We conducted a scoping review of the literature in 3 databases (PubMed, Science Direct and Google Scholar) and included articles published bewteen January 2020 until March 2021. Results: This review included 22 publications that met the inclusion criteria. All articles compared saliva with nasopharyngeal swabs. There were variations of sample collection approach which include type of saliva collected, type of container, the use of presrvative or stabilizing agent, time and volume of saliva collected and requirements for patients prior to sample collection. Moreover, not all study included a detailed information regarding salivary collection methods. Conclusion: Information regarding saliva sample collection and prepartion is required to not only be reproduced by following research but also to determine the best approach for optimal outcome.